2011
DOI: 10.1002/sia.3425
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relation between the secondary yield enhancement and the structure of the metallic overlayer in metal‐assisted SIMS

Abstract: Pristine and Au-covered molecular films have been analyzed by ToF-SIMS for different amounts of evaporated gold. In contrast to other MetA-SIMS studies, the metallization of the high-mass polymers (polycarbonate and polystyrene) was carried out in situ. The evaporation flux was monitored with a quartz-crystal microbalance, and the exact quantity of deposited gold was determined by XPS. It was found that the sticking coefficient of gold on these polymers is less than one. The evolution of the secondary ion yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…We have shown that an enlarged-AuNP surface is useful to increase the SIMS intensity of surface-immobilized peptides, due to a higher binding density of analyte and relevant signal enhancement. Although other SI-enhancing methods have been developed, our study also showed that the SIMS intensity of peptide on the enlarged AuNP was 25-fold higher than that on the AuNP surface at the highest peptide concentration, as in Figures D and . Although the signal enhancement was considerably little (only a factor of 2 higher) when compared to that on the bare Au, the use of AuNPs has more advantages over the bare Au that requires the labor-intensive evaporating steps, because the AuNP-enlarging surface is easily made from as-prepared AuNPs and subsequent chemical treatment, leading to a larger gold surface area in a nanoscale structure.…”
Section: Resultsmentioning
confidence: 58%
“…We have shown that an enlarged-AuNP surface is useful to increase the SIMS intensity of surface-immobilized peptides, due to a higher binding density of analyte and relevant signal enhancement. Although other SI-enhancing methods have been developed, our study also showed that the SIMS intensity of peptide on the enlarged AuNP was 25-fold higher than that on the AuNP surface at the highest peptide concentration, as in Figures D and . Although the signal enhancement was considerably little (only a factor of 2 higher) when compared to that on the bare Au, the use of AuNPs has more advantages over the bare Au that requires the labor-intensive evaporating steps, because the AuNP-enlarging surface is easily made from as-prepared AuNPs and subsequent chemical treatment, leading to a larger gold surface area in a nanoscale structure.…”
Section: Resultsmentioning
confidence: 58%
“…It was indicated that real Au deposition was not homogeneous, but island growth. In addition, deposited Au is considered to make threedimensional nanostructure according to the Volmer-Weber growth mechanism [9] As stated previously, cross-sectioning with the Au plate was performed, and gold was deposited onto the analyzed sections with every sectioning event. Furthermore, increased scanning of the upper section enabled an increase in Au deposition.…”
Section: Resultsmentioning
confidence: 99%
“…A nominal thickness of 2 nm Ag was evaporated onto spin‐coated PS samples for the MetA‐SIMS sample configuration. It has been shown that such small amounts of noble metals deposited onto organic substrates form nano‐islands on the surface because the binding forces among the metal atoms are stronger than those between a metal atom and the organic material . There seems to be either a diffusion of metal particles into the polymer bulk or a migration of organic molecules over the metal clusters .…”
Section: Sample Preparation and Experimental Setupmentioning
confidence: 99%